Fekete-Szegö Problem for a New Class of Analytic Functions - Deepak Bansal (International Journal of Mathematics and Mathematical Sciences)
We consider the Fekete-Szegö problem with complex parameter 𝜇 for the class 𝑅𝜏𝛾(𝜙) of analytic functions.